Implementation of the On The Spot Report Receipt and Verification Program (PVL OTS) by the Indonesian Ombudsman, Bengkulu Province Representative Office - hafifah, elisya putri; suratman, Suratman; Nursanty, Nursanty (Universitas 17 Agustus 1945 Surabaya, 2025)
This research examines the implementation of the On The Spot (PVL OTS) report acceptance and verification program by the Ombudsman RI Bengkulu Representative, which aims to facilitate the public in submitting complaints related to public services. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation. The research subjects comprised the Ombudsman RI Representative of Bengkulu and the community involved in this program. However, there are still challenges and obstacles to implementing this program. Less than optimal offline and online socialization of the program is one of the main obstacles. Furthermore, the number of people accessing services under the PVL OTS program is still low. In addition, budget fluctuations and limited infrastructure also hamper the smooth running of the program. The results showed that the PVL OTS program had been implemented as planned but not optimally. The main obstacles are unclear implementation schedules that depend on the central budget, limited socialization, and limited facilities and infrastructure. Routine evaluations are carried out for each activity, but the applied improvements still need improvement. In conclusion, for the PVL OTS program to run more effectively and efficiently, more structured schedule planning, broader socialization, and provision of adequate facilities and infrastructure are needed.